The sinking of the Lisbon Maru : Britain's forgotten wartime tragedy - Banham, Tony, 1959- (Hong Kong University Press, 2006)
Almost 2,000 British Prisoners of War were aboard the Japanese freighter Lisbon Maru when an American submarine torpedoed and sank her in October 1942. This book tells the story of those men, from the fighting in Hong Kong, through the sinking, and for some, to liberation and beyond. Although never previously studied in any depth, the sinking of the Lisbon Maru was the most costly American on British ""Friendly Fire"" incident of the Second World War. Of the 4,500 of Hong Kong's garrison who perished during the war, 1,000 died directly or indirectly from this sinking. From American, British, H.